2018
DOI: 10.1242/dev.167346
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal dynamics of nuclear RNAi-targeted retrotransposon transcripts in Caenorhabditis elegans

Abstract: Nuclear RNA interference provides a unique approach to the study of RNA-mediated transgenerational epigenetic inheritance. A paradox in the field is that expression of target loci is necessary for the initiation and maintenance of their silencing. How expression and repression are coordinated during animal development is poorly understood. To resolve this gap, we took imaging, deep-sequencing and genetic approaches towards delineating the developmental regulation and subcellular localization of RNA transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Our work links deregulation of the nuclear 22G-RNA pathways to ectopic H3K9 and H3K27 methylation at endogenous genes. Both histone marks can be artificially induced on active genes targeted by exogenous dsRNA (8,31,80), and several H3K9 methyltransferases have been connected to WAGO-induced silencing (30,72,80,81). However, it was not possible to reliably correlate nuclear Argonaute function in inhibiting endogenous genes with H3K9 methylation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Our work links deregulation of the nuclear 22G-RNA pathways to ectopic H3K9 and H3K27 methylation at endogenous genes. Both histone marks can be artificially induced on active genes targeted by exogenous dsRNA (8,31,80), and several H3K9 methyltransferases have been connected to WAGO-induced silencing (30,72,80,81). However, it was not possible to reliably correlate nuclear Argonaute function in inhibiting endogenous genes with H3K9 methylation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…A phylogenetic analysis based on the amino acid sequence of reverse transcriptase indicated that Cer1 - Cer6 retrotransposons fall in the same family domain as the gypsy/Ty3 groups that are adjacent to the family domain that includes HERV-K. Although most of the retrotransposons are silenced by ADARs (adenosine deaminases acting on double-stranded RNA) and nuclear RNAi to protect endogenous genome structure, a few C. elegans retrotransposons have been reported to be actively expressed ( 21 , 22 ). Cer1 produces capsids that assemble virus-like particles (VLPs) in C. elegans germ cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our work links deregulation of the nuclear 22G-RNA pathways to ectopic H3K9 and H3K27 methylation at endogenous genes. Both histone marks can be artificially induced on active genes targeted by exogenous dsRNA (8,31,70), and several H3K9 methyltransferases have been connected to WAGO-induced silencing (30,(70)(71)(72). However, it was not possible to reliably correlate nuclear Argonautes' function in inhibiting endogenous genes with H3K9 methylation (34,35).…”
Section: Discussionmentioning
confidence: 99%